Digital Language Learning in Higher Education: A Critical Literature Review on Teachers' and Students' Challenges - Andi Asrifan; Anita Candra Dewi; Rusydi; Buniati Suman; Haryanto NP; Ramlah (MultiTech Publisher, 2024)
Higher education is using DLL more. Both teachers and students are used to digital learning. We have several digital learning examples. Teacher and student struggles with digital learning, such as using it, persist. This study reviews five-year-old references on digital learning in higher education. The researchers reviewed the literature on digital learning issues in higher education to determine what lecturers and students encounter in teaching and learning. The results suggest that teachers and students encounter issues including readiness to use them. Teachers and students struggle with technology access in different places, thus they should be discussed.